Cyclic Testing of Concrete-Filled Double-Skin Steel Tubular Column to Steel Beam Joint with RC Slab - Dongfang Zhang; Junhai Zhao; Shuanhai He (Advances in Civil Engineering)
The design of composite joints for connecting concrete-filled double-skin tubular (CFDST) columns to steel beams supporting reinforced concrete (RC) slabs is presented in this paper. Five half-scale specimens were designed, including four composite joints with RC slab and one bare steel beam joint, and were tested under a constant axially compressive force and lateral cyclic loading at the top end of the column to evaluate their seismic behavior. The main experimental parameters were the construction of the joint and the type of the column. The seismic behaviors, including the failure modes, hysteresis curves, ductility, strength and stiffness degradation, and energy dissipation, were investigated. The failure modes of the composite joints depended on the joint construction and on the stiffness ratio of beams to columns. Joints of stiffening type had significantly higher load-bearing and deformation capacities than joints of nonstiffening type. Compared with the bare steel beam joint, the bearing capacities of the composite joints with RC slabs were markedly increased. The composite action was remarkable under sagging moments, resulting in larger deformation on the bottom flanges of the beams. Overall, most specimens exhibited full hysteresis loops, and the equivalent viscous damping coefficients were 0.282∼0.311. The interstory drift ratios satisfied the requirements specified by technical regulations. Composite connections of this type exhibit excellent ductility and favorable energy dissipation and can be effectively utilized in superhigh-rise buildings erected in earthquake zones.